"Time's a trap": the poetics of perspective in the Arabian Nights and The Handmaid’s Tale (Colloquia Comparativa Litterarum, 2025)
The essay analyses the dystopian dimension of the framing narrative of the Arabian Nights through the lens of Margaret Atwood’s novel The Handmaid’s Tale, reexamining the heroines’ agency regarding the spatial, temporal and subversive perspectives. It explores the pattern of the night and raises the question of the heroines’ social position and subjectivity through narrative choices and enunciative strategy deployed.
Keywords: Atwood; Shahrâzâd; perspective; nights; dystopia; subversion